Driving Factors of CO2 Emissions: Further Study Based on Machine Learning - Li, Shanshan; Siu, Yam Wing; Zhao, Guoqin (Frontiers in Environmental Science, 2021)
Greenhouse gases especially carbon dioxide (CO2) emissions are viewed as one of the core causes climate change and it has become one of the most important environmental problems in the world. This paper attempts to investigate the relationship between CO2 emissions and economic growth, industry structure, urbanization, research and development (R&D) investment, actual use of foreign capital, growth rate of energy consumption in China between 2000 and 2018. This study is important for China as it has pledged to peak its carbon dioxide emissions (CO2) by 2030 and achieve carbon neutrality by 2060. We apply a suite of machine learning algorithms on the training set of data, 2000-2015, and predict the levels of CO2 emissions for the testing set, 2016-2018. Employing rmse for model selection, results show that the non-linear model of k-nearest neigbors (KNN) model performs the best among linear models, non-linear models, ensemble models and artificial neural networks for the present dataset. Using KNN model, sensitivity analysis of CO2 emissions around its centroid position were conducted. The findings indicate that not all provinces should develop its industrialization. Some provinces should stay at relatively mild industrialization stage while selected others should develop theirs as rapid as possible. It is because CO2 emissions will eventually decrease after saturation point. In terms of urbanization, there is an optimal range for a province. At the optimal range, the CO2 emissions would be at a minimum and it is likely a result of technological innovation in energy usage and efficiency. Moreover, China should increase its R&D investment intensity from the present level as it will decrease CO2 emissions. If R&D reinvestment is associated with actual use of foreign capital, policy makers should prioritize the use of foreign capital for R&D investment on green technology. Last, economic growth requires consuming energy. However, policy makers must refrain from consuming energy beyond a certain optimal growth rate. Above findings provide a guide to policy makers to achieve dual-carbon strategy while sustaining economic development.